Effect of curing temperature on mechanical properties of bio-phenolic/epoxy polymer blends - Ismail, Ahmad Safwan; Jawaid, Mohammad; Hamid, Norul Hisham; Yahaya, Ridwan; Hassan, Azman; Asim, M.; M. Supian, A. B. (Springer, 2022)
Nowadays, researchers continue studies for alternative materials to replace the redundant petroleum-based products. The combination of various polymer mixture process mainly from bio-polymer material as a matrix property could reduce the dependence over petroleum-based polymer, thus the dangerous residue waste from the synthetic polymer in the fabrication process could be eliminated and produce better composite material with lower cost and high performance of composite material in numerous applications. In this study, the effect of bio-phenolic loading and curing temperature on the mechanical properties of bio-phenolic/epoxy polymer blends was investigated. Bio-phenolic/epoxy polymer blends were fabricated with different loading of bio-phenolic resin (5(P-5), 10(P-10), 15(P-15), 20(P-20) and 25(P-25) wt%) and different curing temperature was used which is 100 °C, 130 °C and 150 °C. The overall mechanical properties of bio-phenolic/epoxy polymer blends were improved as bio-phenolic loading increase and curing temperature increase. Obtained results indicated that bio-phenolic/epoxy polymer blends with 20 wt% bio-phenolic at 150 °C showed the highest tensile strength, flexural strength and impact resistance whereas highest tensile modulus and flexural modulus was shown by polymer blend with 25 wt% bio-phenolic at 100 °C and 25wt% bio-phenolic at 130 °C, respectively. It can be concluded that polymer blend with 20wt% bio-phenolic at 150 °C showed overall good mechanical properties. On the basis of finding obtained in this work will be used for further study to fabricate flax fiber/carbon-kevlar reinforced in optimum polymer blends for ballistic helmet applications.